Synthesis, Self‐Assembly, and Nucleic Acid Recognition of an Acylhydrazone‐Conjugated Cationic Tetraphenylethene Ligand. Issue 7 (4th February 2021) - Coste, Maëva; Kotras, Clément; Bessin, Yannick; Gervais, Virginie; Dellemme, David; Leclercq, Maxime; Fossépré, Mathieu; Richeter, Sébastien; Clément, Sébastien; Surin, Mathieu; Ulrich, Sébastien
Abstract: Supramolecular polymers are of interest in the pursuit of multivalent nucleic acids recognition. However, their formation often relies on non‐covalent forces that are also at play in the interaction with nucleic acids. In this work, we designed a novel compound (TPE‐Gir ) combining a tetraphenylethene aromatic core tethered to four quaternary ammoniums through acylhydrazone spacers, and we investigated in detail its self‐assembly and interaction with different types of nucleic acids. The spectroscopic analyses indicate the self‐assembly of regular fluorescent nanoparticles (observed by DLS and TEM) in the absence of nucleic acids, the strong propensity to intercalate into single‐stranded DNA, the ability to bind into the minor groove of double‐stranded DNA, and the selective binding to G‐quadruplex (G4) structures by fitting within a wide G4‐groove. Those recognition events are quantified by isothermal titration calorimetry and the proposed binding models are supported by docking simulations. Abstract : TPE‐Gir self‐assembles into fluorescent nanoparticles and interact with nucleic acids (single‐ and double‐stranded DNA), with selective binding to G‐quadruplexes.